A simulation study on the transport phenomena in ultrafiltration - Gando-Ferreira, Licínio M. (2010)
A coupled model of concentration polarization and membrane transport is used to study the crossflow ultrafiltration of PEG-3400 solutions. For the intramembrane transport, the model incorporates the binary friction model (BFM) derived by Kerkhof [4] and that is a modification of the Maxwell-Stefan-Lightfoot equation. Good agreement between model predictions and experimental data (apparent rejections and pressure drops as function of the flux) has been obtained. A value of 0.49 for the equilibrium partition coefficient K, the only adjustable parameter, was found. The model predictions also enabled us to study the effects of circulation velocity and partition coefficient on the apparent rejection and to get an insight into the concentration profiles in the polarization layer and in the membrane.